Structural assessment of a stone masonry wall using a continuum damage model and experimental validation - Bruno Luís Silva (2007)
Understanding how stone masonry structures behave under dynamic horizontal loads yields important information on possible collapse mechanisms and damage progression along the structure. With this in mind a numerical and experimental study was performed concerning the structural behaviour of a stone masonry wall built in situ at the Laboratory of Seismic and Structural Engineering (LESE). The wall was tested under cyclic horizontal load to simulate the effects of a horizontal seismic action. The experimental response allowed assessing the cyclic behaviour and estimating the energy dissipation and ductility capacity of the structure, as well as its strength and stiffness. Afterwards, the wall was simulated numerically in Cast3M [1] using a finite element modelling strategy. The stones, the infill and the joints were simulated considering them as part of a unique homogeneous material and using a non-linear continuum damage model [2] to reproduce the walls global behaviour. The final objective of this work is to study the applicability of such continuum numerical models to simulate stone masonry structures, using experimental results as reference values.